The challenges in identification of artists-managers: consequences for creativity - Szostak, Michał; Sułkowski, Łukasz (Creativity Studies, 2021)
Research on identity, its tensions and paradoxes have extensive literature and a large number of scientists exploring the subject. Our own experiences in the fields of art and management were the main arguments for the introduce of the concept of “artists-managers” and to undertake research in the area of artists-managers’ identity to find the conclusions for creativity. This article aims to describe the challenges in the identification of artists-managers, who can be crucial in understanding the creativity factor. To reach our goal, we run empirical qualitative research based on in-depth interviews with key-informants from Europe, Africa and North America as well as auto-analysis of an artist-manager identity. We answer the research question “Who is the artist-manager?”. We present our “creativity development model” on the base of artists-managers’ characteristics and we describe what kind of challenges should be considered in the empirical research of artists-managers. These challenges may be used as guidelines for artists-managers: for those who discover an artist-manager in their personality, for defined artists-managers to help to better understand their features, and for artists-managers’ followers to be more sensitive for their leaders’ characteristics. Our model may help to understand and develop the creativity of society.